State Bar of California Annual Meeting Held in Century City - Watkins, Howard::::::::: (1987)
Fresno County Bar Association delegation: Doris Coleman, John Smith, Jack Hames, Herbert Levy, Howard Zidenberg, Robert Oliver, Howard Watkins, Donald Fischbach, Judy Soley, and Mel Richtel; Ventura County delegation in front